Evaluation of the Impact of PSAK 71 Implementation on the Financial Performance of Regional Development Banks: A Comparative Study Before and After the Adoption of the Standard - Rahayu Rahayu; Netty Herawaty; Lutfi Lutfi; Albetris Albetris; Musthafa Luthfi (Greenation International Journal of Economics and Accounting, 2026)
The study uses data from 24 Regional Development Banks (BPD) over a six-year period (2018–2023), consisting of two years before and four years after the implementation of PSAK 71. The ratios examined include Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR). The analysis results indicate that there are significant differences in the ROA and BOPO variables after the implementation of PSAK 71, while the other variables do not show significant changes. These findings suggest that the new accounting standard has a selective impact on indicators of bank financial performance. This study provides empirical contributions for regulators, public accountants, and banking management in understanding the implications of new accounting policies on the stability and efficiency of the banking sector.